2009
DOI: 10.1089/ten.tea.2008.0087
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Laden and Cell-Free Biopolymer Hydrogel for the Treatment of Osteochondral Defects in a Sheep Model

Abstract: The objective of the current study was to determine the suitability of cell-laden and cell-free alginate-gelatin biopolymer hydrogel for osteochondral restoration in a sheep model (n = 12). Four femoral defects per animal were filled with hydrogel (cHG) plus autologous chondrocytes (cHG + C) or periosteal cells (cHG + P) or gel only (cHG) or were left untreated (E). In situ solidification enabled instantaneous implant fixation. Sixteen weeks postoperatively, defect sites were processed for light microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 42 publications
3
40
1
2
Order By: Relevance
“…[29][30][31][32] Approaches under development use chemoattactants to enhance migration of endogenous MSC to accelerate wound healing and/or colonize biomaterial scaffolds. [33][34][35] Recent proof of concept studies demonstrating tissue regeneration by endogenous MSC recruitment have motivated further development of this approach. [36][37][38] The most effective chemoattractants for recruiting endogenous MSC may vary with tissue type and remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Approaches under development use chemoattactants to enhance migration of endogenous MSC to accelerate wound healing and/or colonize biomaterial scaffolds. [33][34][35] Recent proof of concept studies demonstrating tissue regeneration by endogenous MSC recruitment have motivated further development of this approach. [36][37][38] The most effective chemoattractants for recruiting endogenous MSC may vary with tissue type and remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial to establish critical size defects as they do not heal spontaneously. 25,34,35 Our own observations are partly inconsistent: our previous hydrogel study on mature sheep demonstrated that untreated critical size osteochondral defects (diameter: 6 mm, depth: 12 mm) were not restored properly, 36 whereas even larger untreated osteochondral defects (diameter: 8 mm, depth: 13 mm) in another study also on mature sheep showed a healing response (submitted). In order to avoid lesion size as a factor of uncertainty, a decision was made for vast osteochondral defects (width: 6 mm, length: 20 mm, maximum depth: 5 mm).…”
Section: Lesion Size and Animal Modelmentioning
confidence: 89%
“…More than 90% tissue filling was also noted in 2.4-mm [63] and 3.7-mm [41] defects of the rabbit model, which were left untreated for 2 and 3 months, respectively. However, osteochondral defects implanted with hydrogel scaffolds generally have incomplete filling in large animals [14,48]. Differences in repair could be attributed to different intrinsic spontaneous healing capacities between species, as shown by Kon et al who reported the implantation of the same collagen-hydroxyapatite scaffold into sheep [35] and equine [37] models generated inferior fibrocartilaginous tissue in the largersized animal.…”
Section: Discussionmentioning
confidence: 99%